Energy-efficient and QoS-supported deployment strategy of dense Macro-Femto cellular network - Yun LI; Chunsheng WANG; Bin CAO; Qilie LIU (Tongxin xuebao)
With the exponentially increasing of users’ demand for mobile data traffic,massive small cells have been deployed to satisfy the users’ quality of service (QoS) by operators.However,a significant energy would be consumed caused by dense deployment.To this end,a dense heterogeneous cellular network deployment strategy was proposed with QoS guarantee to decline system energy consumption.Firstly,a dense Macro-Femto biased cellular network was used to build the network model,the two QoS indicators of SINR coverage and user average rate was analyzed by stochastic geometry theory.Then,under the condition of QoS constraint,average spatial power consumption (ASPC) was taken as the optimization goal,optimal deploy density and transmission power of Femto were achieved by using optimization theory.Finally,the experimental results show that,comparing with the traditional strategy which only considering base station density,the proposed strategy has advantages in terms of energy efficiency while QoS guarantee.